Public Health Interventions for the COVID-19 Pandemic Reduce Respiratory Tract Infection-Related Visits at Pediatric Emergency Departments in Taiwan - Lin, Chien-Fu; Huang, Ying-Hsien; Cheng, Chi-Yung; Wu, Kuan-Han; Tang, Kuo-Shu; Chiu, I-Min (Frontiers in Public Health, 2020)
Background and objective: Public health interventions such as social distancing, wearing surgical or N95 masks, and handwashing are effective in significantly reducing the risk of infection. The purpose of this article is to analyze the effect of public health interventions on respiratory tract infection-related visits to pediatric emergency departments during the COVID-19 pandemic in Taiwan. Method: Pediatric emergency department visits between January 1 2020 and April 30 2020 were included for trend analysis and compared to the same period during the past three years. The datasets were retrieved from Taiwan National Infectious Disease Statistics System and Kaohsiung Chang Gung Memorial Hospital. Respiratory tract infections with other diagnoses categories, including fever, asthma, and urinary tract infections, were included for subgroup analysis. Result: A significant decrease of more than 50% in respiratory tract infection-related visits was found from February to April 2020 in the national database. With regard to diagnosis category, the proportion of respiratory tract infections in Kaohsiung Chang Gung Hospital also became significantly lower in 2020 during the months of March (43.4% vs. 37.4%, p=0.024) and April (40.1% vs. 32.2%, p<0.001). On the other hand, the proportion of urinary tract infections was significantly higher in 2020 during March (3.7% vs. 5.2%, p=0.033) and April (3.9% vs. 6.5%, p<0.001), and that of asthma was also higher in April (1.6% vs 2.6%, p=0.025). Furthermore, the intensive care unit admission rate was relatively higher in 2020 from February, with significant differences noted in March (1.3% vs. 2.8%, p<0.001). Conclusion: Due to public health interventions for the COVID-19 pandemic, the transmission of not only COVID-19 but also other air droplet transmitted diseases in children may have been effectively prevented.